Factors affecting financial distress in indonesian basic industry and chemicals sector - Susanti; Hartono, Ulil (Jurnal Ilmu Manajemen, 2024)
This research aims to analyse the influence of profitability, leverage, firm size, sales growth, and liquidity on financial distress in companies in the basic industry and chemicals sector listed on the Indonesia Stock Exchange for 2017-2022. The sample for this research is 20 companies in the basic industry and chemicals sector listed on the Indonesia Stock Exchange for 2017-2022 obtained from purposive sampling. The type of data used is quantitative data obtained from secondary data. The data collection technique is a documentation technique obtained from the company's annual financial report from the Indonesia Stock Exchange for 2017 - 2022. The data analysis techniques used are descriptive statistics and logistic regression using SPSS 26. The results of the study show that profitability is proxied by ROA, leverage is proxied by the debt ratio, firm size is proxied by the logarithm of total assets, sales growth is proxied by the sales growth ratio, and liquidity is proxied by the current ratio do not affect financial distress. Advice that can be given to investors and companies is to focus on the five independent variables and internal company factors in looking at the size of financial distress and to consider other possible factors. Apart from that, advice that can be given to future researchers is to use different proxies in carrying out the analysis because different proxies will allow different results to be obtained.